Integrating Governance and Quantitative Evaluation of Resource Management Strategies to Improve Social and Ecological Outcomes. (19th June 2019) - Armitage, Derek R; Okamoto, Daniel K; Silver, Jennifer J; Francis, Tessa B; Levin, Phillip S; Punt, André E; Davies, Ian P; Cleary, Jaclyn S; Dressel, Sherri C; Jones, R Russ; Kitka, Harvey; Lee, Lynn Chi; et al.
Abstract: In this article, we examine how governance can be more effectively integrated with quantitative evaluation methods in applied resource management. Governance refers to how societies organize to make decisions in ways that influence management choices (e.g., harvest allocation), such as levels of participation, the inclusion of different types of knowledge, and legitimacy of processes that lead to decisions. Using a fisheries example, we show that a failure to consider the governance context for quantitative evaluation of alternative management strategies may lead to unexpected consequences or break points in decision-making, bias estimates of risk and returns from management choices, and mask the potential for undesirable social and ecological outcomes.